How productivity can be affected by human capital - Rasli, Mohamad Dzulfiqar; Mohd Nor, Muhammad Zaki Mukhtar; Sorooshian , Shahryar; Tan, Seng Teck; Ismail, Md Yusof (IJEAST, 2016)
In this article we will discuss about how human resources management will affect the productivity. This article will tell about the meaning of human resource management and the meaning of productivity. We also tell the component in the human resource management such as training, incentive and reward that can give impact towards productivity of a company or organization.